A methods engineering study on ROMYNET Enterprises - Garcia, Blessie Marie (College of Engineering, 1999)
ROMYNET Enterprises, a manufacturing firm of resin-bonded ceramics has been chosen as a project study site on the basis of labor content of its work processes. The study, being centered on methods improvement, is a good fit on industries with a considerable labor content in their operations. Methods documentation and analysis is done on actual plant visits, employing various charting tools learned in the methods engineering class. Core problems have been identified to be the following : poor layout, not well-defined organizational structure, lack of policies on work scheduling, poor storage facilities. The group has arrived at alternatives to address the core problems mentioned. For poor layout, two alternatives are generated. In the first alternative, an L-shaped flow of process is installed such that the final process work station is relocated inorder to facilitate immediate delivery. The second alternative permits that the packaging materials are placed nearer the packaging section. In this alternative, space between the dividers is vacated. After cost benefit analysis on the two alternatives, the second alternative has been found viable on the basis of minimum handling, improved worker mobility, least cost and worker safety and morale. To address the issue of a not well defined organizational structure, the study proposes an organizational chart that provides clear job descriptions. By doing this, overlapping functions are minimized and hierarchy of positions turns evident. Two alternatives are generated for the problem on work scheduling. The first policy ensures regular and continuous working time from 8:00 a.m. to 5:00 p.m. with one worker assigned to each task. The second policy makes possible a regular and continuous working time with merged work stations. On the basis of computed capacity based on standard time, alternative 2 comes nearer; reaches the maximum allowable capacity with less idle time of 132.63 minutes as compared to the first alternative's idle time of 320.94 minutes. A vertical rack is designed and installed to facilitate efficient material storage. This rack has rollers for mobility and has a closed back for minimum breakage possibility. The problems mentioned above need careful attention. Addressing such issues enables the company to increase production at the least possible cost without having to sacrifice worker welfare.